Design And Performance Analysis of a Solar-Powered Boost Converter with Inductor Variations Controlled by Arduino Uno - Hardian, Muhammad Paraj Azhar; Ferdyanto, Ferdyanto; Fatwa, Gumilang; Erlangga, Augusta (Department of Physics Education, Universitas Mataram, 2025)
This research designs and makes an analysis of the performance of a solar panel-based DC-DC boost converter topology using an Arduino Uno microcontroller. Boost converter is given a variation of inductor wire with 30 turns and 60 turns using a diameter of 1 . This research was conducted to obtain the highest characteristics and efficiency of the performance of the boost converter that has been designed and made for each inductor wire turn variation. In this research, data analysis will be carried out, namely the effect of duty cycle on voltage and current, and how the effect of variations in the number of inductors turns on the efficiency of the boost converter. This circuit uses an arduino uno microcontroller to generate and control the duty cycle on pulse width modulation (PWM) to regulate and increase the desired output voltage. The inductor on the DC-DC boost converter with a wire variation of 60 turns at a diameter of 1 gets the highest efficiency with an average efficiency of 67.13 , while the inductor wire with 30 turns gets an average efficiency of 66.32 . The maximum voltage generated by the solar panel used as the main source of electrical energy in the boost converter is 20.0 and the control system that has been applied to the arduino uno microcontroller can control and generate a duty cycle with a ratio of 0 - 90 . The boost converter circuit made gets low efficiency due to the presence of MOSFET components that work in non-ideal conditions, which causes excessive power losses.